The effects of type III antifreeze protein and human heat shock protein 70 added to the vitrification medium of mouse embryos on in vitro embryonic development rates - Mustafa Bodu; Mehmet Bozkurt Ataman (Turkish Journal of Agriculture: Food Science and Technology, 2022)
The effect of antifreeze protein type III (AFPIII) and human heat shock protein 70 (HHSP70), added to the vitrification medium of mouse embryos, on post-freeze/thaw in vitro embryonic growth rates and cell numbers were investigated. In total 20 female mice were synchronized. After synchronization, 2 females and 1 male were mated in the same cage. Twenty-four h after mating, the embryos were collected at the pronuclear stage. In total 8 groups were established, including a positive control group (C+), a negative control group (C-), and treatment groups that were vitrified in a medium added with 200, 400 and 800 ng/ml of AFPIII (AFPIII200, AFPIII400, AFPIII800), and 1, 2 and 4 µg/ml of HHSP70 (HHSP70-1, HHSP70-2, HHSP70-4). Solid surface vitrification (SSV) medium was prepared for the vitrification of the embryos. Once thawed, in vitro development rates of embryos were followed at 24, 48, 72 and 96 h. Four embryos, which progressed to the full blastocyst stage, were taken from each group and stained with the Hoeschst 33258 and propidium iodine (PI) dyes to determine the inner cell mass (ICM), trophectoderm (TE) and total cell numbers. The groups showed statistically significant difference for in vitro embryonic development rates at 48, 72 and 96 h (p